PERIODONTITIS A RISK FACTOR FOR PRE-ECLAMPSIA IN PREGNANT WOMEN - MISRATH BANU M.A; JAIGANESH RAMAMURTHY (International Journal of Pharma and Bio Sciences, 2014)
Pre-eclampsia is a life threatening condition which is characterised by hypertension and proteinuia in the pregnant women which occurs after 20 weeks of gestation. When not intervened may lead to eclampsia (seizure). There are many risk factors for preeclampsia one of which is periodontal disease. Periodontal disease is a chronic inflammatory disease condition surrounding the tooth. Periodontitis shows multifactorial disease etiology. Micro-organisms are considered risk indicators of periodontitis. Of all the micro-organisms Porphyromonasgingivalis, Aggregatibacteractionomycetmcomitans, and Fusobacteriumnucleatum are the important bacteria in the periodontal disease. In periodontitis there is release of C-reactive protein, an acute inflammatory mediator. Chronic infection may cause release of cytokines like IL-β. TNF- α, and other mediators like PGE2. These inflammatory mediators are also raised in pre-eclampsia. Acute atherosis is the placental lesion of pre-eclampsia and is characterised by focal endothelial disruption, fibrinoid necrosis of the arterial wall, infiltration of peri-vascular spaces by mononuclear cells and macrophages. The pathology and pathogenesis and clinical setting are similar to atherosclerorosis. Oral pathogens are detected in atherosclerotic plaque where they may play a role in the development and progression of atherosclerosis. Hence these pathogens may also be responsible or may be present in acute atherosis of placenta.